2006
DOI: 10.1021/ma060039+
|View full text |Cite
|
Sign up to set email alerts
|

End-Quenching of Quasiliving Carbocationic Isobutylene Polymerization with Hindered Bases:  Quantitative Formation of exo-Olefin-Terminated Polyisobutylene

Abstract: Polyisobutylenes possessing exclusively exo-olefin end groups were created by end-quenching TiCl 4 -catalyzed quasiliving isobutylene (IB) polymerizations with a hindered base at -60 to -40 °C. Polymerizations were initiated from either 2-chloro-2,4,4-trimethylpentane (TMPCl) or 1,3-bis(2-chloro-2-propyl)-5-tert-butylbenzene, in 60/40 hexane/methyl chloride in the presence of 2,6-dimethylpyridine, allowed to reach 98+% isobutylene conversion, and then reacted with either 2,5-dimethylpyrrole, 1,2,2,6,6-pentamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 33 publications
2
98
0
Order By: Relevance
“…The shoulder (4.82 ppm) to the downfield exo ‐olefin peak at 4.85 ppm (Fig. 1) was attributed either to the product of coupling of two PIB chains28 or rearrangements of growing cations 25…”
Section: Room Temperature Polymerization Of Ibmentioning
confidence: 99%
“…The shoulder (4.82 ppm) to the downfield exo ‐olefin peak at 4.85 ppm (Fig. 1) was attributed either to the product of coupling of two PIB chains28 or rearrangements of growing cations 25…”
Section: Room Temperature Polymerization Of Ibmentioning
confidence: 99%
“…Similarly, Ivan et al 11 described quenching with methallyltrimethylsilane to obtain PIB with exo-olefin end groups. As an alternative, Storey et al 12 have shown that deliberate addition of hindered amines to a TiCl 4 -catalyzed isobutylene polymerization induces β-proton elimination at the chain end for quantitative exo-olefin formation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is a visible shoulder peak (e) at δ = 4.82 to the downfield exo ‐olefin peak (h 1 ) at δ = 4.84 even though MWD of PIB was narrow ( M w / M n = 1.22). This weak resonance at δ = 4.82 may be assigned either to C H 2  protons of internal vinylene resulting from carbenium ion rearrangements or to the two identical protons of C H 2  in the coupled PIBs formed by the addition of a growing PIB carbenium ion (I) to the exo ‐olefinic end group (A) in another PIB chain 29–32. The coupling reactions could not be avoided when β‐proton abstraction from the growing carbenium ions (I) was not sufficiently rapid.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the integral calculation, the PIB chains obtained at −40 °C were only 6.2% of tert ‐Cl terminal groups, and the termination via chlorine transfer from counteranion did hardly take place during polymerization. Instead, the PIB obtained at −40 °C had another 61.9% of exo ‐ (δ f1,2 = 4.64, 4.85 ppm) terminal groups, 20.9% of endo ‐ (δ h = 5.15 ppm) terminal groups due to β‐proton elimination and 11.0% of isomer (δ = 4.82 ppm) C H 2  protons in internal vinylene mainly resulting from carbenium ion rearrangements or in the coupled PIBs formed by the addition of a growing PIB carbenium ion (I) to the exo ‐olefinic end group (A) in another PIB chain 29–32. The serious chain transfer to monomer did also simultaneously take place to form new polymer chains with 67.8% of tert ‐butyl head groups according to the characteristic resonance at δ = 0.99 ppm.…”
Section: Resultsmentioning
confidence: 99%